Digital Media Management as an Innovation of Media Learning in Junior High School - Krety Debora Welong; Deitje Adolfien Katuuk; Jeffry S J Lengkong; Viktory N J Rotty (Tadbir : Jurnal Studi Manajemen Pendidikan, 2023)
This study aims to analyze and describe digital learning management as an innovative learning media at the junior high school or junior high school level. This research is a qualitative research that collects data in the form of a series of descriptions of research results through interviews. Observation and documentation. This research was conducted at Manado I Public Middle School from August 2022 to September 2022. The results showed that planning at SMP Negeri I Manado. Judging from the research results, SMP Negeri I Manado had complete infrastructure according to its functions. And from the results of the documentation of digital tools that are sufficient and support digital media systems in the learning process. The results of the study show that the organization of digital media at SMP Negeri I Manado has been well implemented. The implementation of digital media as an innovative learning media for SMP Negeri I Manado is carried out first by training teachers how to use digital media in learning, then how to use internet sites, websites, videos, sound recordings, music, and Android applications to support and continue to enrich the learning process. . Supervision of digital media at SMP Negeri I Manado is carried out by the principal and teachers, staff and parents of students, to ensure that the use of digital media remains on the expected target, namely to support the learning process and improve student quality. Evaluation of digital media at SMP Negeri I Manado was carried out by analyzing the effect of using digital media in the learning process. So that the evaluation can be used for future program planning.